PENERBITAN SERTIFIKAT HAK ATAS TANAH DI LAUT YANG MENYEBABKAN KONFLIK KEWENANGAN ANTARA LEMBAGA PEMERINTAHAN DI INDONESIA - Akbar, Akbar; Rukman, Auliah Andika; Afdhal, Afdhal (Muhammadiyah Makassar University, 2024)
Indonesia's coastal areas and small islands possess significant natural resource potential but are also vulnerable to various issues, one of which is overlapping authority in the issuance of land title certificates at sea. This jurisdictional conflict can lead to legal uncertainty, environmental degradation, and social disputes.This study employs a prescriptive normative legal research method with a case study approach. It examines relevant land and maritime regulations as well as court decisions to analyze jurisdictional conflicts in the issuance of land title certificates at sea.The research aims to identify and analyze the factors contributing to these jurisdictional conflicts and provide recommendations for resolving them. The findings indicate that conflicts arise due to overlapping regulations, unclear territorial boundaries, differing interpretations, and a lack of coordination among relevant government agencies. The issuance of land title certificates at sea that are legally and administratively flawed may be annulled through legal proceedings involving the courts and land authorities.Harmonizing land and maritime regulations is crucial in addressing these conflicts. The overlapping and inconsistent legal frameworks must be resolved immediately. Additionally, clarifying the jurisdictional boundaries between land and sea is an essential step, as clear demarcations will eliminate uncertainty and conflicts regarding institutional authority. Public awareness and education on land and maritime regulations must also be enhanced, ensuring that communities understand their rights and obligations concerning coastal land, as well as the processes and procedures for obtaining land title certificates at sea.Keyword: Certificate, Authority, Conflict, Government Institution, Indonesia